Maize seed quality with fungicide treatment during the storage period. Issue 1 (November 2021) - Rahmawati,; Aqil, Muhammad
Abstract: In some areas, farmers sometimes delay planting due to several factors, including: unfavorable climate, unprepared land and insufficient manpower so that planting takes a long time. As a result, seeds that have been given a fungicide cannot be planted and stored under uncontrolled conditions, both at the place and temperature of the storage room. Therefore, the purpose of this study was to determine the storage resistance of seeds that have been given a fungicide (saromyl) so that they can be used as a reference for storing seeds of saromyl. The research was carried out in June - December 2020 at the seed quality testing laboratory of the Cereal Crops Research Institute (Balitsereal), Maros, South Sulawesi Province. The corn seeds used in the study were Bisma 2018 and 2019, Sukmaraga 2017 and 2019, Srikandi Kuning 2018 and 2019, Lamuru 2017 and 2019 varieties. Observations were made on 1000 grain weight, moisture content, electrical conductivity, maximum growth potential, seed growth speed, length of primary root, length of shoot and number of secondary roots. This study used a completely randomized design with 4 replications. The results showed that at room temperature storage (25-26°C and relative humidity 50-58%) the seeds that had been given a fungicide (saromil) with a storage period of 21 days still had high seed quality. Even at low temperature storage (18-18.9°C and Rh 50-55%) during the 6-month storage period, the quality of the seeds was very good. The shelf life of seeds that have been given a fungicide (saromil), is influenced by the shelf life of the seeds, the temperature and relative humidity of the storage room.